2018
DOI: 10.1111/dmcn.13797
|View full text |Cite
|
Sign up to set email alerts
|

Children with cerebral palsy in Ghana: malnutrition, feeding challenges, and caregiver quality of life

Abstract: Results. The prevalence of malnutrition was very high: 65% of children aged <5 years were categorised as underweight, 54% as stunted and 58% as wasted. Reported difficulties with child's feeding were common and was associated with the child being underweight (Odds Ratio 10.7 95% CI 2.3-49.6) and poorer caregiver quality of life (p<0.001). No association between caregiver quality of life and nutritional status was evident.Interpretation: There is a need for appropriate, accessible caregiver training and support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 36 publications
9
46
1
4
Order By: Relevance
“…Some aspects of mealtimes and feeding their child were improved. Other studies have similarly highlighted the particular challenges of feeding for children with disabilities, including children with cerebral palsy [30, 4750], and our baseline study showed feeding difficulties were also strongly associated with poorer caregiver QoL and child malnutrition [51]. Yet few studies have evaluated interventions aimed at improving nutritional outcomes for these children in low resource settings: we only found one study in Bangladesh study demonstrated improvements in nutritional outcomes through parental support and training, exclusively focussed on a feeding intervention [30].…”
Section: Discussionmentioning
confidence: 63%
“…Some aspects of mealtimes and feeding their child were improved. Other studies have similarly highlighted the particular challenges of feeding for children with disabilities, including children with cerebral palsy [30, 4750], and our baseline study showed feeding difficulties were also strongly associated with poorer caregiver QoL and child malnutrition [51]. Yet few studies have evaluated interventions aimed at improving nutritional outcomes for these children in low resource settings: we only found one study in Bangladesh study demonstrated improvements in nutritional outcomes through parental support and training, exclusively focussed on a feeding intervention [30].…”
Section: Discussionmentioning
confidence: 63%
“…Community implementers need to be better equipped with the knowledge to assess and refer children with CP. There may be an argument for blanket referral of all children with CP to nutrition services (Polack et al., ). These services need to be aware that deviation from standard protocols will likely be required when managing these cases, such as recognizing that children with CP may need to consume RUTF that has been modified in its consistency or to be provided with non‐peanut‐based RUTFs, which are less harmful to the lungs, if aspirated (Adams, ).…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative study was nested within a larger before/after study seeking to evaluate the impact of the community‐based parent CP training program: GTKCP. Findings from this wider evaluation are published separately (Polack et al., ; Zuurmond et al., ). This qualitative study used semistructured interviews with primary caregivers of children with CP, both prior to (“baseline”) and after 12 months of implementing the training manual (“end line”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 42 studies included an estimated total of 23 169 participants. The number of participants per study ranged from 30 to 14 806, with a median participant number of 120 (interquartile range [IQR] 55-186): 30≤n<50 (n=8 studies); 29,[33][34][35][36][37][38]49 n<100 (n=10 studies); 39,[42][43][44]47,48,50,63,64,69 n<200 (n=14 studies); [30][31][32]40,41,46,[51][52][53]61,62,65,67 n<500…”
Section: Participantsmentioning
confidence: 99%